2015
DOI: 10.1111/hdi.12342
|View full text |Cite
|
Sign up to set email alerts
|

Chronic obstructive pulmonary disease in patients with end‐stage kidney disease on hemodialysis

Abstract: The objectives of this study were to assess the prevalence of chronic obstructive pulmonary disease (COPD) in hemodialysis patients with spirometry and to examine the effects of fluid removal by hemodialysis on lung volumes. Patients ≥18 years at two Danish hemodialysis centers were included. Forced expiratory volume in one second (FEV1 ), forced vital capacity (FVC), and FEV1 /FVC ratio were measured with spirometry before and after hemodialysis. The diagnosis of COPD was based on both the GOLD criteria and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…Additionally, there is growing literature about the prevalence of chronic obstructive pulmonary disease (COPD) in patients with CKD (11,12). Notwithstanding etiology, hypoxemia and hypoxia are associated with a host of acute and chronic sequelae affecting multiple organ systems (13)(14)(15), including the cardiovascular system (16,17), wound healing (18), proinflammatory pathways (19), and the central nervous system (20).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there is growing literature about the prevalence of chronic obstructive pulmonary disease (COPD) in patients with CKD (11,12). Notwithstanding etiology, hypoxemia and hypoxia are associated with a host of acute and chronic sequelae affecting multiple organ systems (13)(14)(15), including the cardiovascular system (16,17), wound healing (18), proinflammatory pathways (19), and the central nervous system (20).…”
Section: Introductionmentioning
confidence: 99%
“…Plesner et al (26) examined changes in spirometry parameters in COPD patients undergoing dialysis in 2016 and found that improvement in the FEV1/FVC ratio and FEV1 was significantly related to patients' ultra-filtrated volume; furthermore, when this volume was more than 0.3 of the body weight, a significant improvement in the FEV1/FVC ratio and FEV1 was seen. This is while in our study, there was no relationship between ultra-filtrated volume and spirometry parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Renal disease and renal failure are two leading causes of the global burden of diseases and important causes of death in developing countries. Chronic kidney disease (CKD) is considered one of the main global health issues due to its high prevalence, progression to end-stage renal disease (ESRD), and early death (1)(2)(3)(4). CKD emanates from various renal damages and is an irreversible, progressive disease that may progress gradually and lead to the loss of renal function and ESRD (5).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the effects of hemodialysis in COPD patients with end‐stage renal disease also deserve to be mentioned. Although dyspnea is frequently observed among patients on hemodialysis, respiratory causes of dyspnea often remain unrecognized . On average, hemodialysis does not increase forced vital capacity and FEV 1 among COPD patients unless a critical threshold of fluid removal, likely at least 3% of bodyweight, is achieved .…”
Section: Ckd In Patients With Copd: Clinical and Prognostic Relevancementioning
confidence: 99%
“…Although dyspnea is frequently observed among patients on hemodialysis, respiratory causes of dyspnea often remain unrecognized . On average, hemodialysis does not increase forced vital capacity and FEV 1 among COPD patients unless a critical threshold of fluid removal, likely at least 3% of bodyweight, is achieved . Accordingly, close cooperation between pulmonologists and nephrologists is highly desirable for the optimal management of these complex patients.…”
Section: Ckd In Patients With Copd: Clinical and Prognostic Relevancementioning
confidence: 99%